Construção de um trabalho audiovisual como metodologia de ensino do emprego das funções orgânicas no cotidiano - Queiroz, Sergio de Oliveira (2020)
The teaching of organic chemistry in the use of organic functions in everyday life is a very broad topic, which can be contextualized with the use of digital resources in the production of audiovisual work as a complementary teaching and learning methodolo gy. In the digital age, it is possible to observe that students, digital natives, relate to people through new media such as blogs and social networks. In this context, it is possible to create a contextualized approach to virtual teaching through informat ion and communication technologies, bringing to the student a teaching learning methodology more appropriate to this reality. This work is an exploratory research, aims to approach Organic Chemistry in a contextualized way in classes of 2nd year of High Sc hool, to create audiovisual works at the Military College of the Fire Department of Ceará in Fortaleza, with the help of a virtual teaching room. The work consisted of creating six groups of students with five members each, in three different rooms, totali ng eighteen groups to develop works on the use of organic functions in daily life. Six organic functions were proposed and drawn at random, one for each group, where they should develop a research on the theme: Use of organic functions in daily life. Assoc iating it to a specific organic function as an object of study. The surveys were developed in a virtual classroom, where a team member at a time described the content of the meetings in a digital field notebook at a time, so that they could follow up, guid e and suggest the progress of the research. This research enabled the school's students to prepare several audiovisual works that served as the basis for the last global test of the year. The use of audiovisual language as a complementary teaching learning methodology had the purpose of making chemistry teaching more interactive and updated, improving school performance, a fact that occurred with the increase in grades throughout 2018 compared to previous years, as well as the positive percentage performanc e of the participating classes in relation to a control class.